Big data benchmarks, performance optimization, and emerging hardware : 6th Workshop, BPOE 2015, Kohala, HI, USA, August 31-September 4, 2015, revised selected papers /: 6th Workshop, BPOE 2015, Kohala, HI, USA, August 31-September 4, 2015, revised selected papers. (2016) - Unknown
No abstract available